(untitled) (Sirte University Journal of Humanities, 2026)
Amid the rapid proliferation of artificial intelligence now acting as a social agent reshaping the very nature of human relationships this study examines how algorithms, social robots, and intelligent platforms have transformed core concepts such as trust, intimacy, and belonging. Face-to-face interactions have increasingly given way to digital exchanges mediated by systems that lack genuine consciousness or authentic emotions. The analysis reveals that, despite AI’s ability to convincingly mimic human behavior, it remains devoid of moral intention and true empathy, resulting in superficial connections that create an illusion of closeness while deepening social isolation. A key finding of the research is that trust in digital relationships no longer stems from mutual empathy or shared responsibility, but from unconscious algorithms lacking ethical intent rendering it a functional illusion stripped of human depth. Accordingly, the study recommends establishing clear ethical safeguards to prevent AI systems from being presented as genuine substitutes for human relationships. It further emphasizes the importance of revitalizing physical spaces that foster face-to-face interaction to reclaim the essence of authentic human connection. The paper concludes with an urgent call for collective ethical frameworks that ensure technology remains a servant to humanity not a replacement for the core of human relationality.